Utilization of High-Power Leds as Non-Invasive KV Meter Detectors in Collimation of Lighting - Moch BAgus Fatihul Ihsan; Moch Prastawa Assalim Tetra Putra; Lamidi Lamidi; I Dewa Gde Hariwisana; Tribowo Indrato; Singgih Yudha Setiawan; Mansour Asghari (Department of electromedical engineering, Health Polytechnic of Surabaya, Ministry of Health Indonesia, 2022)
X-ray radiation is used to diagnose the human body. Two parameters are often used as settings when using this machine. The first is the KV value, and the second is the mA value. If an error occurs in the kV setting, it will cause inappropriate image quality, so that it will provide inaccurate information in patient examination. Likewise with the presence of excessive doses to the patient's body. To ensure that the KV value that comes out is in accordance with the settings on the machine consul, invasive and non-invasive measurements can be carried out. Non-invasive is becoming an easy standard to do. Several types of equipment on the market and research results have been widely used for this non-invasive activity. The problem is that currently the existing tools still use detectors at an expensive price. The purpose of this study was to design a low-cost non-invasive x-ray KVmeter detector using an LED detector and test the ability of the detector at each point of collimation.. The method used in this study is to stump the detectors placed at 4 ends of the collimation 20 cm apart. The data is taken by doing x-ray exposure at a distance of 60 cm. The module measurements were carried out under 80 mA exposure conditions for 1 second and a collimation area of ​​20 x 20 cm. X-ray exposure settings were performed at 40kV, 50kV, 60kV, and 70kV settings. The module measurement results are compared with the x-ray machine setting values. From the comparison results, the smallest error rate on Sensor 2 is 0.83% while the highest error is on S5 of 26.43%. The results can be concluded that the LED phosphor can capture x-rays, but the detector is weak due to interference from ambient light. The results obtained from the detector itself are still less stable and linear. In future research, stability and linearity will be built using a mechanical design that reduces ambient light interference.